Alcohol as a cancer risk factor - Godlewski, Dariusz; Wojtyś, Piotr; Bury, Przemysław (Contemporary Oncology/Współczesna Onkologia, 2000)
In 1988 the International Agency for Research on Cancer (IARC) analyzed and summarized the available data on alcohol consumption and the related risk of cancer development [1]. The results of the majority of studies analyzed at the time pointed to the conclusion that in the case of certain cancer sites alcohol consumption is directly related to their incidence rates. Further epidemiological analyses confirmed this assumption. This publication, drawing on worldwide sources, presents a synthetic review of the most important studies concerning the impact of alcohol beverages consumption on the risk of cancer development. The impact of this factor on the incidence of alcohol-related cancers, such as cancers of stoma, pharynx, larynx, esophagus and liver.